2016
DOI: 10.1190/geo2015-0684.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rock frame weakening using time-lapse crosswell: The Frio brine pilot project

Abstract: [Formula: see text] injection into subsurface reservoirs leads to pressure and saturation changes. Furthermore, [Formula: see text]-brine-minerals interaction could result in dissolution or reprecipitation of rock frame-forming minerals. Observed time-lapse seismic associated with [Formula: see text] injection into poorly consolidated sandstone at the Frio [Formula: see text] injection site (Texas, USA) could not be predicted using classical rock-physics models (i.e., models involving elastic changes in the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Such transport was suggested by Al Hosni et al. (2016) in explaining why the magnitude of the time‐lapse effect due to the injection of CO 2 into the Frio C sand at the Frio CO 2 injection site was greater than predicted using conventional rock physics models.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Such transport was suggested by Al Hosni et al. (2016) in explaining why the magnitude of the time‐lapse effect due to the injection of CO 2 into the Frio C sand at the Frio CO 2 injection site was greater than predicted using conventional rock physics models.…”
Section: Discussionmentioning
confidence: 72%
“…This may make it easier for grain contacts to slip and for fluid flow to dislodge and transport grains in the Frio case than in the Paluxy sandstone, particularly if CO 2 acts to weaken any cement that may be present at the grain contacts. Such transport was suggested by Al Hosni et al (2016) in explaining why the magnitude of the time-lapse effect due to the injection of CO 2 at the Frio CO 2 injection site was greater than predicted using conventional rock physics models.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In an acidic environment created by CO 2 injection, the impact of water -rock reaction on rock mechanical properties may be very obvious. For instance, at the Frio test site in the United States, a reduction of approximately 30% in rock shear modulus (characterized by P-wave velocity) was observed after CO 2 injection, much more than originally anticipated (Al Hosni et al, 2016). Subsequent analysis indicated that this was due to the reduction of aqueous pH by CO 2 injection, which triggered the dissolution of cementing minerals in the rock (Xu et al, 2010;Ilgen and Cygan, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Time‐lapse seismic imaging has been shown to be an effective technique for subsurface CO 2 monitoring for both enhanced oil recovery [ Lazaratos and Marion , ; Majer et al ., ; White , ] and sequestration [ Arts et al ., ; Xue et al ., ; Daley et al ., ; Gareth and Chadwick , ; Ajo‐Franklin et al ., ]. For example, time‐lapse crosswell tomographic velocity estimates of the Frio‐I CO 2 plume demonstrated a seismic velocity decrease up to 500 m/s within the plume that were caused by the injection of supercritical CO 2 into the brine reservoir [ Hovorka et al ., ; Ajo‐Franklin et al ., ; Daley et al ., ; Al Hosni et al ., ]. For the expected advanced role of monitoring in the future, e.g., for the accounting of CO 2 emissions [ Benson , ], there is a demand for seismic monitoring to provide early detection of leaks and quantitative estimation of the amount of CO 2 in the storage zone.…”
Section: Introductionmentioning
confidence: 99%